Biogenic enabled in-vitro synthesis of nickel cobaltite nanoparticle and its application in single stage hybrid biohydrogen production. (December 2021) - Srivastava, Neha; Mohammad, Akbar; Srivastava, Manish; Syed, Asad; Elgorban, Abdallah M.; Bahadur Pal, Dan; Mishra, P.K.; Yoon, Taeho; Gupta, Vijai Kumar
Graphical abstract: Highlights: In vitro biogenic synthesis of NiCo2 O4 NPs using Emericella variecolor NS3. Evaluation of NiCo2 O4 NPs on thermal and pH stability of crude enzyme. NPs stabilized crude enzyme hydrolyzed rice straw yields 51.7 g/L reducing sugars. Single stage hybrid fermentation using Bacillus subtilis PF_1 and Rhodobacter sp. Hybrid fermentation produces 2978 mL/L cumulative H2 after 336 h. Abstract: In biomass to biofuels production technology enzyme plays a key role. Nevertheless, the high production cost of cellulase enzyme is one of the critical issues in the economical production of biofuels. Nowadays, implementation of nanomaterials as catalyst is emerging as an innovative approach for the production of sustainable energy. In this context, synthesis of nickel cobaltite nanoparticles (NiCo2 O4 NPs) via in vitro route has been conducted using fungus Emericella variecolor NS3 meanwhile; its impact has been evaluated on improved thermal and pH stability of crude cellulase enzyme obtained from Emericella variecolor NS3. Additionally, bioconversion of alkali treated rice straw using NiCo2 O4 NPs stabilized cellulase produced sugar hydrolyzate which is further used for H2 production via hybrid fermentation. Total 51.7 g/L sugar hydrolyzate produced 2978 mL/L cumulative H2 production after 336 h along with maximum rate 34.12 mL/L/h in 24 h using Bacillus subtilis PF_1 and Rhodobacter sp. employed for dark and photo-fermentation, respectively.